2022
DOI: 10.1007/s00181-022-02297-3
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate governance affect financial analysts’ stock recommendations, target prices accuracy and earnings forecast characteristics? An empirical investigation of US companies

Abstract: This paper investigates how corporate governance quality affects the analyst’s stock recommendations, forecast efficiency and target price accuracy on New York Stock Exchange. In particular, as corporate governance is often uncertain and ambiguous to investors, expert financial advisors may use transparent corporate governance information to set their recommendations and improve the level of accuracy of their earnings forecasts. According to agency and signaling theories, good governance mechanisms aim to miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…The efficient market theory states that investors cannot use publicly available information, such as historical stock price or trading volume, to find excess returns in the stock market [ 60 ]. An understanding of how the behavioral characteristics of investors affect the mechanism of information transmission in the money market and capital market prices needs to be improved; and essential to the decision-making of financial analysts and investors by asking companies to significantly improve the information environment in good times and bad [ 65 ].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The efficient market theory states that investors cannot use publicly available information, such as historical stock price or trading volume, to find excess returns in the stock market [ 60 ]. An understanding of how the behavioral characteristics of investors affect the mechanism of information transmission in the money market and capital market prices needs to be improved; and essential to the decision-making of financial analysts and investors by asking companies to significantly improve the information environment in good times and bad [ 65 ].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Additionally, Ref. [25] have presented evidence supporting the positive impact of robust shareholder rights on financial reporting quality [40][41][42][43][44][45].…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 99%
“…The results showed that various privacy protection requirements cannot be met by the data identi cation algorithm and the privacy protection algorithm related to legal oversight mechanisms suggestion in. [23]. The study aims to understand the relation between analysts'assessment and the quality of governance using a sample of American companies and a database of recommendations and pro t forecasts presented by analysts who are unique in their expectations.…”
Section: B Recommendations In Investmentmentioning
confidence: 99%